Peer Tutoring as a Strategy for Enhancing Student Academic Performance in Statistics and Probability: A Systematic Review from an Educational Economics Perspective - Anane, Emmanuel Agyei (PT. Batari Edu Calya, 2024)
This study aims to examine the effectiveness of the peer tutoring strategy in enhancing the academic performance of high school students in Statistics and Probability. Employing a Systematic Literature Review (SLR) approach, this study analyzes relevant scholarly publications over the past decade. The review findings indicate that the implementation of peer tutoring consistently yields positive impacts on student academic achievement, particularly in quantitative learning contexts. From an educational economics perspective, this strategy is considered efficient as it optimizes internal school resources without necessitating significant additional costs. Peer tutoring also contributes to increased learning productivity and a reduction in failure rates. Therefore, peer tutoring is recommended as a viable alternative teaching method suitable for widespread implementation in the context of economics and mathematics education.